Pathological and compensatory reactions in the blood system of small rodents exposed to chronic low dose ionizing radiation - A. I. Lypska; N. K Rodionova; N. M. Riabchenko; O. O. Burdo; V. A. Shytiuk (Âderna Fìzika ta Energetika)
Changes in the blood systems of small rodents inhabiting for many generations the Chornobyl Exclusion Zone territories with a relatively low level of radionuclide pollution were studied. Animals’ calculated absorbed doses were in the low dose and dose rate ranges. Dual changes in the blood system were registered, damaging as well as reactive, and high variability of hematological and cytogenetic indicators was observed. Identified changes may be caused by the cumulative effects of chronic radiation exposure.